Communicating Anti Bullying Educational Messages For Elementary School Student Through Board Game Storyline - Widyasari; Aditya Rahman Yani; Eki Cahya Imani (Nusantara Science and Technology Proceedings, 2020)
Bullying behavior in elementary school children is increasing daily, following the current development of the digital era. It has become one of the most important cases to be followed up on because it can negatively affect the children's morals and it can also hurt others. Therefore, as an effort to tackle bullying cases, it is necessary to deliver innovative anti-bullying educational messages to children at the elementary school level, in hopes that children will become more interested, and will be easier to absorb the educational messages. Innovative anti-bullying educational messages can be delivered through an interesting and fun storyline of the board game media. The steps used to construct this research are identifying the problem or phenomenon, primary and secondary data collection, and analyzing the primary and secondary data using the Questioning Method of 5W + 1H (What, Why, Who, Where, When, How ) to compile anti-bullying educational messages for elementary school children which are packaged attractively through the storyline of a board game. This study concludes that there was three rating weight of anti-bullying actions carried out by elementary school children, namely mild, moderate, and severe. Each rating weight of anti-bullying has five forms of bullying so that there are 15 forms of bullying in total. Each bullying act is then processed into a case study in the form of questions on the board game, with a question model that intentionally touches the empathy of elementary school children. Each question has three positive answer options with different levels of anti-bullying (levels 1, 2, and 3). These levels of anti-bullying are the points that will be obtained by each player (level 1 = 1 point, level 2 = 2 points, level 3 = 3 points). If the player gets a total of 15 points as minimum points, then the player is considered to have low anti-bullying action if the player gets a total of 15-30 points, then the player is considered to have moderate anti-bullying action, and if the player gets a total of 30-45 points, then players are considered to have high anti-bullying actions. These total points are the rewards on this board game.